2019
DOI: 10.1016/j.ajhg.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Mitochondrial and Nuclear Mitochondrial Variants and Genes with Seven Metabolic Traits

Abstract: Mitochondria (MT), the major site of cellular energy production, are under dual genetic control by 37 mitochondrial DNA (mtDNA) genes and numerous nuclear genes (MT-nDNA). In the CHARGEmtDNAþ Consortium, we studied genetic associations of mtDNA and MT-nDNA associations with body mass index (BMI), waist-hip-ratio (WHR), glucose, insulin, HOMA-B, HOMA-IR, and HbA1c. This 45-cohort collaboration comprised 70,775 (insulin) to 170,202 (BMI) pan-ancestry individuals. Validation and imputation of mtDNA variants was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
85
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 143 publications
10
85
0
Order By: Relevance
“…Mitochondrial function is regulated not only by the genes encoded in mtDNA but also by those in nDNA. As these two types of genes confer synergistic biological functions 6 , co-evolution of the genetic variants embedded within them 5 , namely "mtDNA-nDNA genotype association", has been suggested 17 . Thus, we tested the hypothesis that there might exist preferential transmission between nDNA and mtDNA at a genotype level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial function is regulated not only by the genes encoded in mtDNA but also by those in nDNA. As these two types of genes confer synergistic biological functions 6 , co-evolution of the genetic variants embedded within them 5 , namely "mtDNA-nDNA genotype association", has been suggested 17 . Thus, we tested the hypothesis that there might exist preferential transmission between nDNA and mtDNA at a genotype level.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested mtDNA genetics risk on late-onset human clinical phenotypes 15,17,35 . In addition to validation of the previously suggested associations with renal functions, our study provided novel phenotypic associations in creatine kinase, an immune-related disease, and a liver function-related trait.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence supporting a hypothesis whereby gene variants in mitochondrial DNA (mtDNA) and mitochondrialfunction-related nuclear DNA contribute to insulin resistance and T2D 90 or abnormal exercise-induced responses 91 . Gene variants in mitochondrial-function-related nuclear DNA lead to relatively mildly impaired mitochondrial function, whereas classical mtDNA gene variants typically cause a severe reduction in mitochondrial function with neurological deficits and β-cell failure.…”
Section: Insulin Resistance In Skeletal Musclementioning
confidence: 99%
“…The presented patient had hyperlipidemia, which is commonly attributed to the alimentary habits of an individual. However, hyperlipidemia can be also a manifestation of a MID, which is frequently not appreciated. Elevated serum lipids in MID patients may represent a compensatory mechanism to provide fuel for alternative generation of adenosine triphosphate.…”
mentioning
confidence: 99%